2014
DOI: 10.1007/s10439-014-1028-2
|View full text |Cite
|
Sign up to set email alerts
|

Transmural Variation and Anisotropy of Microvascular Flow Conductivity in the Rat Myocardium

Abstract: Transmural variations in the relationship between structural and fluid transport properties of myocardial capillary networks are determined via continuum modelling approaches using recent three-dimensional (3D) data on the microvascular structure. Specifically, the permeability tensor, which quantifies the inverse of the blood flow resistivity of the capillary network, is computed by volume-averaging flow solutions in synthetic networks with geometrical and topological properties derived from an anatomically-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 33 publications
3
36
1
Order By: Relevance
“…The magnitudes of the errors in these values from the converged permeability ‫ܭ(‬ ) range from around 25 % to 1.6 %. This is in contrast to the error in the mean calculated by Smith et al which has a maximum value of around 70 % for a 100 x 100 x 21.6 µm 3 voxel (Smith et al, 2014). The lack of a sharp increase in permeability at smaller cube sizes is likely to be due to the more random, isotropic nature of the cerebral microvasculature, as opposed to the more aligned myocardial capillaries modelled by Smith et al It is also likely that the much larger density of the longitudinally aligned myocardial capillaries will have partially accounted for this difference.…”
Section: Permeability Of Capillary Networkcontrasting
confidence: 70%
See 4 more Smart Citations
“…The magnitudes of the errors in these values from the converged permeability ‫ܭ(‬ ) range from around 25 % to 1.6 %. This is in contrast to the error in the mean calculated by Smith et al which has a maximum value of around 70 % for a 100 x 100 x 21.6 µm 3 voxel (Smith et al, 2014). The lack of a sharp increase in permeability at smaller cube sizes is likely to be due to the more random, isotropic nature of the cerebral microvasculature, as opposed to the more aligned myocardial capillaries modelled by Smith et al It is also likely that the much larger density of the longitudinally aligned myocardial capillaries will have partially accounted for this difference.…”
Section: Permeability Of Capillary Networkcontrasting
confidence: 70%
“…It was found that the permeability of the capillaries in the three principal directions was highly isotropic, with less than 1.2 % variation in their converged values. This was due to the "mesh-like" structure of the capillary network, and confirms that when modelling the cerebral microvasculature a 2-dimensional simplification of the model is not a valid assumption, unlike when modelling coronary capillary networks (Smith et al, 2014).…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations